Polygenic and developmental profiles of autism differ by age at diagnosis - Xinhe Zhang; Jakob Grove; Yuanjun Gu; Cornelia K. Buus; Lea K. Nielsen; Sharon A. S. Neufeld; Mahmoud Koko; Daniel S. Malawsky; Emma M. Wade; Ellen Verhoef; Anna Gui; Laura Hegemann; et al. (Nature, 2025)
Abstract Although autism has historically been conceptualized as a condition that emerges in early childhood 1,2 , many autistic people are diagnosed later in life 3–5 . It is unknown whether earlier- and later-diagnosed autism have different developmental trajectories and genetic profiles. Using longitudinal data from four independent birth cohorts, we demonstrate that two different socioemotional and behavioural trajectories are associated with age at diagnosis. In independent cohorts of autistic individuals, common genetic variants account for approximately 11% of the variance in age at autism diagnosis, similar to the contribution of individual sociodemographic and clinical factors, which typically explain less than 15% of this variance. We further demonstrate that the polygenic architecture of autism can be broken down into two modestly genetically correlated ( r g = 0.38, s.e. = 0.07) autism polygenic factors. One of these factors is associated with earlier autism diagnosis and lower social and communication abilities in early childhood, but is only moderately genetically correlated with attention deficit–hyperactivity disorder (ADHD) and mental-health conditions. Conversely, the second factor is associated with later autism diagnosis and increased socioemotional and behavioural difficulties in adolescence, and has moderate to high positive genetic correlations with ADHD and mental-health conditions. These findings indicate that earlier- and later-diagnosed autism have different developmental trajectories and genetic profiles. Our findings have important implications for how we conceptualize autism and provide a model to explain some of the diversity found in autism.